Enhancement of acetate-induced apoptosis of colorectal cancer cells by cathepsin D inhibition depends on oligomycin A-sensitive respiration - Alves, Sara (2024)
Colorectal cancer (CRC) is a leading cause of death worldwide. Conventional therapies are available with varying effectiveness. Acetate, a short-chain fatty acid produced by human intestinal bacteria, triggers mitochondria-mediated apoptosis preferentially in CRC but not in normal colonocytes, which has spurred an interest in its use for CRC prevention/therapy. We previously uncovered that acetate-induced mitochondrial-mediated apoptosis in CRC cells is significantly enhanced by the inhibition of the lysosomal protease cathepsin D (CatD), which indicates both mitochondria and the lysosome are involved in the regulation of acetate-induced apoptosis. Herein, we sought to determine whether mitochondrial function affects CatD apoptotic function. We found that enhancement of acetate-induced apoptosis by CatD inhibition depends on oligomycin A-sensitive respiration. Mechanistically, the potentiating effect is associated with an increase in cellular and mitochondrial superoxide anion accumulation and mitochondrial mass. Our results provide novel clues into the regulation of CatD function and the effect of tumor heterogeneity in the outcome of combined treatment using acetate and CatD inhibitors.